Association of ADHD and Obesity in Hispanic Children on the US-Mexico Border: A Retrospective Analysis - Salcido, Alyssa; Robles, Eden Hernandez; Chaudhary, Kiran; Alvarado, Luis; Iñiguez, Sergio D.; Vargas-Medrano, Javier; Diaz-Pacheco, Valeria; Villanos, Maria Theresa; Gadad, Bharathi S.; Martin, Sarah L. (Frontiers in Integrative Neuroscience, 2022)
Pediatric obesity and Attention Deficit Hyperactivity Disorder (ADHD) are rising health concerns in the United States, especially among Hispanic children and adolescents. Research on Hispanic children and adolescents indicates disproportionately higher prevalence rates of obesity in the this community but scant data on ADHD prevalence rates. In contrast, a plethora of research studies across the general population examines the relationship between childhood obesity and ADHD. In addition, there is a lack of research that examines the role of ethnicity and sub-ethnic group correlations in ADHD, particularly in the Hispanic population. Existing studies in the general population indicate ADHD may be a risk factor for being overweight compared to normal controls. The objective of the present study is to examine the prevalence of obesity in children with ADHD compared to children in the general population in a predominately Hispanic sample on the US-Mexico border. A total of 7,270 pediatric medical records were evaluated. The retrospective analysis included Body Mass Index (BMI) and related health variables, and ethnicity and showed that children with ADHDare more likely to be, . In conclusion, no significant relationship existed between obesity and ADHD among Hispanic children on the US-Mexico Border, and instead we found the opposite correlation.